2018
DOI: 10.1158/1078-0432.ccr-17-1872
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MYCN–PARP–DNA Damage Response Pathway in Neuroendocrine Prostate Cancer

Abstract: Purpose: We investigated MYCN-regulated molecular pathways in castration-resistant prostate cancer (CRPC) classified by morphologic criteria as adenocarcinoma or neuroendocrine to extend the molecular phenotype, establish driver pathways, and identify novel approaches to combination therapy for neuroendocrine prostate cancer (NEPC).Experimental Design and Results: Using comparative bioinformatics analyses of CRPC-Adeno and CRPC-Neuro RNA sequence data from public data sets and a panel of 28 PDX models, we iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 29 publications
5
76
1
Order By: Relevance
“…Another potential mechanism underlying the essential function of HP1a in NEPC aggressiveness is that HP1a depletion impaired DNA damage response (DDR) machineries, which is in accordance with previous studies (46,47). Most recently, another study also reported that a DDR pathway is enriched in NEPC, contributing to NEPC cell proliferation (48). Overall, HP1a could potentially serve as a therapeutic target for effective management of developed NEPC.…”
Section: Discussionsupporting
confidence: 88%
“…Another potential mechanism underlying the essential function of HP1a in NEPC aggressiveness is that HP1a depletion impaired DNA damage response (DDR) machineries, which is in accordance with previous studies (46,47). Most recently, another study also reported that a DDR pathway is enriched in NEPC, contributing to NEPC cell proliferation (48). Overall, HP1a could potentially serve as a therapeutic target for effective management of developed NEPC.…”
Section: Discussionsupporting
confidence: 88%
“…It has become a truism that sustaining proliferation is an important hallmark of cancer [22]. c-MYC has been founded an elevated expression in PCa and multiple studies shown c-MYC can induce tumor cells proliferation and regulate cell cycle though MYC-responsive genes [7,[23][24][25]. Cell cycle genes expression level has been founded that associate with the timing of PCa metastasis, as an independent factor [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study by Zang et al indicates that ELL2 has an important role in DNA damage response and repair. This enables ELL2 loss to function like a double edge sword which on one hand can induce prostate carcinogenesis, and on the other can sensitize cells to radiation therapy [41]. Human kallikrein-related peptidase 2 (KLK2, previously known as hK2) is a secreted serine protease from the same gene family as PSA.…”
Section: Discussionmentioning
confidence: 99%